Migration and Mental Health in Mexico: Domestic Migrants, Return U.S. Migrants, and Non-Migrants - Donato, Katharine M.; Caron, Laura; Hamilton, Erin (Frontiers in Psychiatry, 2020)
In this paper, we use survey data from the Mexican Retrospective Demographic Survey (Encuesta Demográfica Retrospectiva) and National Survey of Households (Encuesta Nacional de Hogares) collected in 2017 to examine self-reports of depression, anxiety, chronic fatigue, and pain among domestic migrants, eturned U.S. migrants, and non-migrants. Although self-reports do not always correspond to clinical diagnoses, they offer some insight into mental health, especially for those without a diagnosis because of limited access to services or stigma. Regression results reveal that domestic migrants, e.g. those who moved within Mexico, reported more anxiety, chronic fatigue, and pain, but risks for U.S. migrants were comparable to non-migrants, controlling for other characteristics. Findings from the decomposition analysis help explain these findings. While domestic migrant vs. non-migrant differences result both from different migrant demographic attributes, such as age and gender, and differences in the effects of these characteristics between the groups, U.S. migrant vs. non-migrant differences in anxiety and pain emerge only after allowing for the relationship between each observed characteristic and the mental health outcome to vary. Thus, compared to domestic migrants, U.S. migrants are selected on characteristics associated with good mental health—they are positively selected—but those characteristics are not protective for them.